A Mild and Selective Reduction of β‐Lactams: Rh‐Catalyzed Hydrosilylation towards Important Pharmacological Building Blocks. Issue 9 (17th February 2015) - Bornschein, Christoph; Lennox, Alastair J. J.; Werkmeister, Svenja; Junge, Kathrin; Beller, Matthias
Abstract: Four‐membered N‐heterocyclic compounds exhibit a broad range of pharmacological activities. Herein, we report a useful rhodium‐catalyzed protocol for the activation of phenylsilane to reduce tertiary β‐lactams. Reaction with the tertiary amides was selective over secondary amides, esters, olefins and nitriles, with no erosion of stereochemistry. A one‐pot protocol from commercially available starting materials and a selective reduction of a complex penicillin derivative demonstrate the synthetic utility of this facile procedure. Abstract : A selective Rh‐catalyzed protocol to reduce β‐lactams to important pharmacologically active azetidines is presented. Reaction with tertiary amides was selective over secondary amides, esters, olefins and nitriles, with no erosion of stereochemistry. A one‐pot protocol from commercially available starting materials and a selective reduction of a complex penicillin derivative demonstrate the high synthetic utility of this procedure.